Legends and liturgy in the Old English prose Andreas. (26th November 2014) - Friesen, Bill
Abstract: This article examines liturgical language and motifs potentially interwoven with the Old English prose account of 'St Andrew amongst the Cannibals', located in Cambridge, Corpus Christi College 198. The article traces in detail the possible parallels between the liturgy of the Mass and the language of the account, and then considers explanations for liturgical elements in the saintly legend and what this may contribute to our aesthetic understanding of that account.